2009
DOI: 10.1002/app.29698
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium‐based layered silicate—Poly(ethylene terephthalate) nanocomposites: Stability, thermal and mechanical properties

Abstract: PET-clay nanocomposites were prepared using alkyl quaternary ammonium and phosphonium modified clays by melt-mixing at 280 C using a micro twin screw extruder. The latter clays were prepared by synthesizing phosphonium surfactants using a simple onestep method followed by a cation exchange reaction. The onset temperature of decomposition (T onset ) for phosphonium clays (>300 C) was found to be significantly higher than that of ammonium clays (around 240 C). The clay modified with a lower concentration (0.8 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 23 publications
1
31
1
Order By: Relevance
“…The M n is decreased approximately 48% and 51% by inclusion of 1 wt% Cloisite 30B and RM-Cloisite 30B in the PET matrix, respectively. This observation is opposite to the findings whereby the more OMMT that is introduced into the IIPC process, the greater the increase in molecular weight of the PET nanocomposite [17,18]. The findings in the current work verify that the addition of nanoclay particles probably causes some steric hindrance for the in situ interlayer polymerization and as a result shorter polymer chains with lower molecular weights are formed.…”
Section: Effect Of Modified and Remodified Clays On Intrinsic Viscosicontrasting
confidence: 99%
See 1 more Smart Citation
“…The M n is decreased approximately 48% and 51% by inclusion of 1 wt% Cloisite 30B and RM-Cloisite 30B in the PET matrix, respectively. This observation is opposite to the findings whereby the more OMMT that is introduced into the IIPC process, the greater the increase in molecular weight of the PET nanocomposite [17,18]. The findings in the current work verify that the addition of nanoclay particles probably causes some steric hindrance for the in situ interlayer polymerization and as a result shorter polymer chains with lower molecular weights are formed.…”
Section: Effect Of Modified and Remodified Clays On Intrinsic Viscosicontrasting
confidence: 99%
“…As can be noticed, with increasing either the Cloisite 30B or the RM-Cloisite 30B content in the PET matrix, the position of the exothermic peaks is gradually shifted, whereas the peaks become moderately narrower and sharper. The DT c values of PETCNs are in the range of [14][15][16][17][18] C, which are narrower than that for pure PET (about 26 C), indicating that the added nanoclay particles act as effective heterogeneous nucleating agents that significantly enhance the crystalline structures as their loading is increased. It is also suggested that nanoclay itself can help the PET molecules stack on each other in order to grow into crystallites, thus leading to the higher crystallization rate [24].…”
Section: Crystallization and Melting Behaviorsmentioning
confidence: 99%
“…Since PLA is a fairly polar polymer, the increased hydrophobicity and strong π -π interactions between neighboring phenyl groups likely decreased the ability for PLA to enter the galleries. Similar behavior has been observed in poly(ethylene-co-terephthalate) composites containing alkyltriphenylphosphonium exchanged clays (23). Fluorescence measurements were used to assess the applicability of NB exfoliation monitoring in PLA.…”
Section: Effects Of Surfactant Headgroupsupporting
confidence: 57%
“…In order to investigate the hydrophobicity of the samples, the experiment was performed on samples as received (not dried). Evaporation of free water (an indication of hydrophobicity) in clay results in an initial mass loss below 200 C; while, evaporation of structural water under dehydroxylation causes a mass loss between 570 and 700 C in the unmodified clay [20,28,29]. There was no other significant mass loss for unmodified clay up to 570 C. In the case of 30B organoclays, however, the major mass loss occurred in the temperature range of 240-420 C. Quaternary ammonium ions presented in 30B clays started to degrade at the onset of decomposition temperature (T 0 ) of 240 C. This temperature is below the PET processing temperature of 300 C. Significant increases in T 0 were observed for clays modified with C1C4-Im and 3C6C14-Ph to give values of 375 C and 490 C, respectively.…”
Section: Thermal Gravimetric Analysismentioning
confidence: 99%